체형측정 방법에 따른 사상체질 진단정확률 비교 연구 - 김종원(Jong Won Kim); 설유경(Yu Kyung Sul); 최재중(Jae Jung Choi); 권석동(Suk Dong Kwon); 김규곤(Kyu Kon Kim); 이용태(Yong Tae Lee) (동의생리병리학회지, 2007)
For Objectivity development of the body shape that is an importance standard for the classification of sasang constitutional medicine diagnosis, We made a comparison between Automatic & Physical measuring. This study uses 2 attitude which lies down & standing. We measured the body of patients(Width 5 places and circumference 8 places) and analyzed the anthropometric data dividing into sex, age, BMI. 296 patients's data are used in the analysis.